Heidegger and Deconstruction - Lazić, Nebojša J. (Collection of Papers of the Faculty of Philosophy in Priština, 2017)
Thanks to Jacques Derrida, Martin Heidegger’s philosophical thought played a significant role in the emergence of postmodern thought about literature, that is, deconstruction. Although largely transformed by Derrida, Heidegger’s original ideas can still be recognized in the critical texts of the Yale School. In the case of Slavoj Žižek, Derrida’s appeal to write for writing’s sake led to the uncontrolled (textual) activities of this author. Furthermore, we have determined that the works of Paul de Man have a deeper connection with Heidegger’s basic ideas than the works of other representatives of this methodological orientation.